Interpersonal Communication Strategies between Parents and Children Under the Age of 12 Years in Preventing Online Game Addiction in Manado City - Sondakh, Mariam; Kawengian, Debby D.V.; Onsu, Reiner R. (Newinera Publisher, 2023)
Abstract In today's era of technology and information, people cannot be separated from the use of the internet, including children. Since the Covid-19 pandemic until now, many children carry out their activities at home, and the use of the internet in children has increased in intensity, which is used as a source of learning and entertainment information. Nowadays many children under the age of 12 years who spend hours playing and addicted to online games. Many negative impacts arise due to online game addiction in children. Therefore, a parent's interpersonal communication strategy is needed to prevent online game addiction in children. The results showed that interpersonal communication strategies between parents and children in preventing online game addiction in Manado City, especially in Malalayang District and Tikala District, namely: Carrot Swinging Strategy: controlling children by providing rewards or rewards in the form of clothes, shoes, maimaikan, food, etc. Dependent Sword Strategy: in the form of punishment to unravel or restrict children from playing online games. Catalysing Strategy: Parents in communicating include rational arguments according to rationality so that children are willing to change attitudes or behaviors as they wish. Siamese Twin Strategy: Parents involve themselves in activities that they encourage children to do together. and Fantasy World Strategy: The parent directs the child's behavior, first creating a certain fantasy in the child's mind and then directing it to the behavior as the parent wants.